Vitellogenin receptor mediates heat adaptability of oocyte development in mud crabs and zebrafish - Long Zhang; Kun Wu; Haoyang Li; Minwen Zhan; Sheng Wang; Enhui Song; Qi Zhang; Jian He; Xinyi He; Menghuang Xu; Hengwei Deng; Yingchun Su; et al. (Nature Communications)
Abstract Climate-driven warming affects the reproduction of oviparous ectotherms. However, whether oviparous ectotherms possess a protection mechanism against heat stress for oocyte development, which is essential for maintaining the continuity of animal populations, is largely unknown. Under high temperatures, female mud crabs (Scylla paramamosain) typically have well-formed ovaries, while a few crabs were found to experience oocyte development failure. To investigate the heat stress protection mechanism of oocyte development in mud crabs, we construct a chromosome-level genome of this species and identify an enhancer of the vitellogenin receptor (VtgR) that stimulates its expression under high temperatures. Lacking this enhancer due to an intronic deletion leads to low VtgR expression in abnormal crabs, resulting in abnormal vitellogenic oocyte formation in these individuals when exposed to high temperatures. Furthermore, we identify a similar heat stress protection mechanism in zebrafish. Disruption of Lrp13, a VtgR-like protein in zebrafish, results in impaired vitellogenin absorption and ovarian degeneration in zebrafish exposed to high temperatures. Our results reveal a VtgR-mediated mechanism that protects vitellogenic oocyte formation against heat stress in mud crabs and zebrafish, contributing to their heat adaptability during oocyte development.